2020
DOI: 10.1177/2031952520905145
|View full text |Cite
|
Sign up to set email alerts
|

The legal and jurisprudential evolution of the notion of employee

Abstract: The essay analyses the concept of employed worker in the light of the expansive trend of labour law. Two perspectives are investigated. The first concerns the revisiting of the concept of employed worker through the interpretation of jurisprudence. Comparative analysis demonstrates a tendency, not univocal but prevalent, of jurisprudence to broaden the notion of subordinate work, which manifests itself through purposive interpretation techniques. The other perspective is that of the creation of intermediate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…zonom bez sindikata. 55 57 S druge strane, kontroverzni Electronic Arts u Njemačkoj koji se oslanja na druge oblike formalnog zastupanja gospodarskih i socijalnih interesa radnika kao što je Vertrauensteam ("tim od povjerenja") koji se čini spornim jer takav ex gratia oblik predstavništva zaobilazi djelovanje radničkog vijeća. 58 S obzirom na to da je rad u industriji videoigara karakteristično privremen i nestabilan očekivano se stvara opće stanje straha koje odvraća radnike da se učlane u sindikate što dodatno pojačava njihovu ranjivost.…”
Section: Digitalizacija Rada I Fleksibilni Oblici Zapošljavanjaunclassified
“…zonom bez sindikata. 55 57 S druge strane, kontroverzni Electronic Arts u Njemačkoj koji se oslanja na druge oblike formalnog zastupanja gospodarskih i socijalnih interesa radnika kao što je Vertrauensteam ("tim od povjerenja") koji se čini spornim jer takav ex gratia oblik predstavništva zaobilazi djelovanje radničkog vijeća. 58 S obzirom na to da je rad u industriji videoigara karakteristično privremen i nestabilan očekivano se stvara opće stanje straha koje odvraća radnike da se učlane u sindikate što dodatno pojačava njihovu ranjivost.…”
Section: Digitalizacija Rada I Fleksibilni Oblici Zapošljavanjaunclassified
“…Riders are connected via smartphone to the delivery app. From this they receive precise information about the time, place and direction of the delivery (Perulli 2020). On the other side, the employer is able to gather and process various data through the IoT network: locations, timing, interaction with other riders.…”
Section: Prohibition Of Forced Labourmentioning
confidence: 99%
“…The way practices evolve requires research, and the informal legal prescript interpretive process has been shown to account for substantive legal meanings (Stappert, 2020). In a way, the PI can be a form of document content analysis that refers to the "grammatical, systematic, teleological, and historical examination of the legislation" (Kommers, 1989, p. 49;Du Plessis, 2015Perulli, 2020. The communicative contents of different utterances of sentences can vary and require interpretation within a specified context (Fallon, 2019).…”
Section: Pi Preceding Multiple-party Data Collection Proceduresmentioning
confidence: 99%